Anxiety and Depression in Adolescents Before and During Covid-19 - Rini Nur Diana; Mamnuah; Yekti Satriyandari; Andari Wuri Astuti; Dwi Ernawati (International Journal of Public Health Excellence (IJPHE), 2023)
COVID-19 pandemic affects various group age, one of them in the group teenager as many as 27% of youth experience anxiety, 15% depression During pandemic, 46% youth no motivated for do usual activity they like it, 36% don't motivated for do profession home, and 43% youth woman feel pessimistic regarding his future. Temporary teenager man feel pessimistic that is about 31%. Method study in study this use method quantitative descriptive, with result state internet usage to be predictor depression, anxiety and stress. There is suspension of study and transition to online learning has in a manner significant Upgrade Internet use among teenager of an average of 5.46 hours a day before happened the COVID-19 pandemic to 9.74 hours a day moment the COVID-19 pandemic. Besides that in study [2] get results that the COVID-19 pandemic can exacerbate mental health experienced by adolescents. Specifically enhancement score anxiety 4.39 times more high in adolescents. One the cause is slowdown economy and parental unemployment that can influence parental mental health so that persecute his son, so could Upgrade problem adolescent mental health.